REPRESENTATION OF CAPITALISM IN DIGITAL ADVERTISING AND ITS IMPACT ON LIFESTYLE - Rafi Rivaldi Akbar; Dicky Prastyo; Eko Purwanto (Global Journal of Management, Accounting, and Financial Studies, e-ISSN: 3109-1539, 2025)
Research This aiming to study representation ideology capitalism in digital advertising as well the impact to formation style life consumptive society . Using approach qualitative with method studies literature , research This analyze various source For identify digital advertising delivers values capitalistic through narrative , visuals, and personalization data- based . Research results show that digital advertising no only promote products , but also in active construct style ideal life that is materialistic , individualistic , and oriented towards social status . Social media and algorithms play a role significant in strengthen effect psychological advertising , especially in the younger generation young , which leads to culture consumptive excessive and potential impact psychological negative . Research This conclude that critical media literacy is solution important For increase awareness and reduce influence negative digital advertising